Sexual violence as a limiting factor on the perception and management of the risk of HIV in women married to migrants - Yesica Yolanda Rangel Flores
ABSTRACT Objective: to analyze the influence of sexual violence on the perception and management of the risk of HIV in women married to migrants. Methods: study with an ethnographic approach carried out in urban and rural communities. Data were obtained by methodological triangulation, with participant and non-participant observation, as well as interviews. The informants were 21 women married to international migrants. The interviews were transcribed and discourse analysis was applied to them. Results: three categories emerged from the speeches to problematize the influence of sexual violence in the perception and management of the risk of HIV: "Characterization of sexual practices in the context of migration", "Experiences of sexual violence" and "Construction of the risk of HIV-AIDS". Conclusion: women have difficulty to recognize the acts of sexual violence in their daily lives, and their perceptions of risk are not decisive in the management of the threat to which they are exposed. Therefore, it is becoming increasingly urgent that nursing problematizes the sexual violence within "steady couples", as a challenge to the promotion of healthy lifestyles.